TGF-β-associated extracellular matrix genes link cancer-associated fibroblasts to immune evasion and immunotherapy failure. Issue 1 (December 2018) - Chakravarthy, Ankur; Khan, Lubaba; Bensler, Nathan; Bose, Pinaki; De Carvalho, Daniel
Abstract The extracellular matrix (ECM) is a key determinant of cancer progression and prognosis. Here we report findings from one of the largest pan-cancer analyses of ECM gene dysregulation in cancer. We define a distinct set of ECM genes upregulated in cancer (C-ECM) and linked to worse prognosis. We found that the C-ECM transcriptional programme dysregulation is correlated with the activation of TGF-β signalling in cancer-associated fibroblasts and is linked to immunosuppression in otherwise immunologically active tumours. Cancers that activate this programme carry distinct genomic profiles, such asBRAF, SMAD4 andTP53 mutations andMYC amplification. Finally, we show that this signature is a predictor of the failure of PD-1 blockade and outperforms previously-proposed biomarkers. Thus, our findings identify a distinct transcriptional pattern of ECM genes in operation across cancers that may be potentially targeted, pending preclinical validation, using TGF-β blockade to enhance responses to immune-checkpoint blockade. Changes in ECM are of predictive value in pancreatic and colorectal cancer prognosis. Here, the authors perform a pan-cancer analysis and find a subset of ECM genes that is linked to TGF-β signalling signature and is correlated with immunotherapy failure.